JAIN IRRIGATION: VICTORIOUS JOURNEY FROM FALL TO RISE (Proceedings of the International Conference on Sustainable Management for Peace and Harmony, 2025)
This case study examines the remarkable journey of Jain Irrigation Systems Limited (JISL) from a severe financial crisis to a successful corporate turnaround and recovery. The study analyzes the company's transformation from the edge of bankruptcy in 2018-2019, when it faced a debt burden of over ₹5,000 crores, to its recent recognition as one of India's most valuable family businesses in 2024. Through comprehensive debt restructuring, strategic operational improvements, and renewed focus on core competencies, JISL successfully implemented a turnaround plan that resulted in significant financial recovery, with net profit soaring from a loss of ₹12.1 billion in FY23 to a profit of ₹9.1 billion in FY24. The case provides insights into crisis management, financial restructuring, and the importance of stakeholder cooperation in corporate recovery scenarios. Key success factors include unanimous lender support, strategic asset optimization, working capital management improvements, and maintaining operational excellence during financial distress.
Keywords: corporate turnaround; debt restructuring; financial crisis management; agricultural industry; family business recovery